2001
DOI: 10.1002/1521-3765(20010716)7:14<3078::aid-chem3078>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Lanthanide Amides as Homogeneous Catalysts for Alkyne Hydroamination and the Tishchenko Reaction

Abstract: The homoleptic bis(trimethylsilyl)amides of Group 3 metals and lanthanides of the general type [Ln[N(SiMe3)2]3] (1) (Ln=Y, lanthanide) represent a new class of Tishchenko precatalysts and, to a limited extent, precatalysts for the hydroamination/cyclization of aminoalkynes. It is shown that 1 is the most active catalyst for the Tishchenko reaction. This contribution presents investigations on the scope of the reaction, substrate selectivity, lanthanide-ion size-effect, and kinetic/mechanistic aspects of the Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(82 citation statements)
references
References 75 publications
1
80
1
Order By: Relevance
“…However, it took several days to complete the reaction, and the catalysts are expensive and difficult to prepare. Berberich and Roesky [12] , and Bürgstein et al [13] found that lanthanide silylamides Ln[N(SiMe 3 ) 2 ] 3 are among the best catalyst precursors for this reaction, and the reaction can be …”
Section: Resultsmentioning
confidence: 99%
“…However, it took several days to complete the reaction, and the catalysts are expensive and difficult to prepare. Berberich and Roesky [12] , and Bürgstein et al [13] found that lanthanide silylamides Ln[N(SiMe 3 ) 2 ] 3 are among the best catalyst precursors for this reaction, and the reaction can be …”
Section: Resultsmentioning
confidence: 99%
“…Successful intermolecular transformations include ynone synthesis,23 cross‐aldol reactions,24 coupling of isocyanides with terminal alkynes,25 dimerization of terminal alkynes,26 guanylation of amines,27 hydrosilylation,28 hydroboration,29 Tishchenko aldehyde dimerization,30and amidations 31. Intramolecular transformations include hydroelementation processes, such as hydroamination,32, 30b hydrophosphination,20b and hydroalkoxylation 33. In regard to organolanthanide‐mediated tandem hydrofunctionalization processes, several very efficient and selective hydroamination/CC bond formation sequences have been reported [e.g., Eq.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lanthanide amides are active catalysts for a variety of olefin and alkyne transformations, including hydroamination/cyclization [1,2], hydroalkoxylation/cyclization [3], ethylene polymerization [4,5], hydrosilylation [6], the addition of terminal alkynes to nitriles [7], the monocoupling reaction of isocyanides with terminal alkynes [8]. They are also found to be the catalysts for the polymerization of polar monomers, such as methylmethacrylate [9][10][11], phenylisocyanate [12], e-caprolactone and lactide [13,14], as well as for the Tishchenko reaction [15,16], guanylation of amines with carbodiimides [14], amidation of aldehydes with amines [17], and Mannich-type reaction [18]. etc.…”
Section: Introductionmentioning
confidence: 99%